TINJAUAN ASUPAN GIZI DAN KONDISI FISIK PEMAIN SEPAKBOLA TIGO JANGKO FOOTBALL CLUB (FC) KECAMATAN LINTAU BUO KABUPATEN TANAH DATAR - Muhammad Arif; Hastria Effendi; Arif Fadhli Mukhlis (JURNAL STAMINA, 2019)
The problem in this study was that there was still a lack of nutritional intake and the low physical condition of football players Tigo Jangko FC in Lintau District Buo Tanah Datar District. This study aims to determine the nutritional intake and physical condition of football players Tigo Jangko FC District Lintau Buo Tanah Datar District. This research is a descriptive type of research. The results of this research were all 25 Tigo Jangko FC soccer players. Samples were taken by means of "purposive sampling", which is 11 people. The instrument for nutritional intake with a 24-hour food recall form was used to determine nutrient intake and energy. Physical conduction measured in each physical element is, Durability measured by Bleep Test, leg muscle power measured by leg dynamometer, Speed ​​measured by 50 meter sprint, Agility measured by Shuttle Run Test, Explosive muscle leg strength measured by Vertical Jump and flexibility measured by sit and reach. Data analysis techniques were carried out using descriptive analysis.The results of the analysis of nutritional intake and physical conditions, namely, 1) The average level of adequacy of macro nutrients Tigo Jangko FC soccer players per day, for carbohydrates in the less category, protein in the less category and fat in the normal category. 2) Overview of VO2Max which is dominantly owned by Tigo Jangko FC soccer players is 33.8 - 42.5 classified as medium category (63.64%). 3) Overview of the dominant leg muscle strength possessed by soccer players Tigo Jangko FC is 127.50 - 187.49 classified as the medium category (54.55%). 4) Overview of the dominant speed possessed by football players Tigo Jangko FC is 3.92 - 4.34 classified as good category (36.36%). 5) The dominant review of agility possessed by Tigo Jangko FC soccer players is 14.97 - 16.39 which is categorized as less (45.45%). 6) Vertical jump review which is dominantly owned by football player Tigo Jangko FC is 54 - 114 classified as less category (72.73%). 7) A review of the dominant flexibility possessed by soccer player Tigo Jangko FC 11.5 - 19 is categorized as good (63.64%).